Mixing characteristics of multiple impacting jets - Wang, Zhenwei. (2013)
For decades, the conventional idea of pollution remediation through jet plume is based on high speed jets and entrainment of ambient water into the flow profile to effect of dispersion and dilution. However, there may be possibility in creating larger mixing volume through the interaction of converging jets which in the pollution affected vicinity. This experimental investigation aims at establishing the fluid dynamics characteristics of converging pipe jets, and ultimately, assessing on its velocity distributions for the diverse group of equipment and technology which required the attention of pipe jets properties. In this study, the student will develop the velocity distributions characteristic model for a three dimensional converging pipe jets set at an inclined angle of 60° on similar plane, utilising the Particle Image Velocimetry (PIV) measurement methodology. The focus will be put on the centreline maximum velocity decay rate and axial velocity distribution in the spanwise and transverse plane respectively, and also, the spreading characteristics will be studied in details. The centreline maximum velocity decayed linearly after a streamwise distance of approximately 8.5D from the discharge point and experimental data assumed self-similarity profile at the location further downstream of the discharge point. Gaussian profiles were observed on the spanwise plane while a “dual-peak” profile was observed on the transverse plane. The boundary edges established by velocity field widths in the transverse direction depicted a linear and parabola relationship on the X-Y plane and X-Z plane respectively. In addition, the evolution of velocity spreading width on the X-Y plane was slightly larger than those of either a single round jet or a single plane jet while the spreading width on the X-Z plane projected almost twice the size of its counterpart (X-Y).